Karakteristik Ibu dengan Kelengkapan dan Ketepatan Pemberian Imunisasi Dasar Bayi di Wilayah Kerja Puskesmas X - Said, Fathia Fakhri Inayati; Sari, Putri Permata; Yeni, Roza Indra (MAHESA : Malahayati Health Student Journal, 2024)
ABSTRACT The completeness and accuracy of providing basic immunization to babies is one indicator of improving the quality and quality of implementation of immunization programs which is characterized by minimal drop out rates, so it is necessary to know the characteristics of mothers that influence the completeness and accuracy of immunization. The aim of this research is to determine the relationship between maternal characteristics and the completeness and accuracy of providing basic immunization to babies. The research design used was cross sectional with a sample size of 36 people, determining the sample size using the total sample. Data collection uses questionnaires to determine characteristics and observation sheets for behavior. The data above outlines the characteristics of respondents with a sample size of 36. Based on the data above, the highest age is 26 - 35 with a percentage (55.5%), high school education level 13 (36.11%), type of work who are not working 23 (63.8%). ), Number of Children 2 12 (33.33%), Distance from home <500 Meters 25 (69.4%), Good Level of Knowledge 30 (83.33%), Positive Mother's Attitude 30 (83.33%). Good maternal behavior 31 (86.11%), complete immunization completeness 31 (86.11%) and inappropriate immunization accuracy 22 (61.11%) Conclude that between age, education, level of knowledge, occupation, number of children, distance from home , attitudes and behavior of mothers regarding the completeness and accuracy of providing basic immunizations to babies in the working area of Puskesmas. Keywords: Mother, Completeness and Accuracy of Basic Immunization  ABSTRAK Kelengkapan dan ketepatan pemberian Imunisasi dasar pada bayi merupakan salah satu indikator peningkatan mutu dan kualitas pelaksanaan program imunisasi yang ditandai dengan minimnya angka drop out, sehingga diperlukan untuk mengetahui karakteristik ibu yang mempengaruhi kelengkapan dan ketepatan imunisasi.  Tujuan penelitian ini diketahui hubungan karakteristik ibu dengan kelengkapan dan ketepatan pemberian imunisasi dasar pada bayi. Desain penelitian yang digunakan adalah Cross sectional  dengan jumlah sampel 36 orang, penentuan besar sampel dengan menggunakan total sampel.  Pengumpulan data menggunakan kuesioner untuk mengetahui karakteristik dan lembaran observasi untuk perilaku. Data di atas megamarkan karateristik responden dengan jumlah sampel 36 Berdasarakan data di atas Umur tertinggi 26 – 35 dengan presentase (55,5 %), Tingkat Pendidikan SMA 13 (36,11 %), Jenis Pekerjaan Yang tidak bekerja 23 (63,8%), Jumlah Anak 2  12 (33,33%),  Jarak rumah <500 Meter 25 (69,4%), Tinglat Pengetahuan  Baik 30 (83,33%), Sikap Ibu Positif 30 (83,33%). Perilaku ibu baik 31 (86,11%), Kelengkapan Imunisasi lengkap 31 (86,11%) dan ketepatan Imunisasi tidak tepat 22 (61,11%) Simpulkan bahwa antara umur, pendidikan, tingkat pengetahuan, pekerjaan, jumlah anak, jarak rumah, sikap dan perilaku ibu dengan kelengkapan dan ketepatan pemberian imunisasi dasar pada bayi di wilayah kerja Puskesmas X. Kata Kunci: Ibu, Kelengkapan Dan Ketepatan Imunisasi Dasar